The impact of healthcare industry convergence on the performance of the public health system: a geospatial modeling study of provincial panel data from China - Li, Wei; Zhu, Ke; Liu, Echu; Peng, Wuzhen; Fang, Cheng; Hu, Qiong; Tao, Limei (Frontiers in Public Health, 2023)
Objective: This paper examines the impact of healthcare industry convergence on the performance of the public health system in the eastern, central, and western regions of China.Methods: Public health performance was measured by a composite index of three standards: average life expectancy at birth, perinatal mortality, and maternal mortality. The healthcare industry convergence was measured using a coupling coordination degree method. The spatial lag, spatial error, and spatial Durbin models were used to estimate the effect of healthcare industry convergence on public health system performance and this effect's spatial dependence and heterogeneity across eastern, central, and western China using panel data from thirty Chinese provinces from 2002 to 2019.The convergence of the healthcare industry significantly promotes regional public health (  =0.576, 95% CI: [0.331,0.821]). However, the convergence does not have a spatial spillover effect on the public health system at the national level. Additionally, analysis of regional heterogeneity shows that the direct effects of healthcare industry convergence on public health are positive and statistically significant for Eastern China, statistically insignificant for Central China, and positive and statistically significant for Western China. The indirect effects are negative, statistically significant, positive, statistically significant, and statistically insignificant for these three regions, respectively. This is a provisional file, not the final typeset article Conclusions: Policy efforts should strengthen the convergence between the healthcare industry and relevant industries. It can produce more current healthcare services to improve public health and reduce regional health inequality.